Price competition, inter-firms relationships, bank discrimination and wage inequalities: a post keynesian perspective - Jordan Melmiès; Thomas Dallery (Revue de la Régulation)
The article analyses the impact of price competition on inter-firms relationships, bank discrimination and wages inequalities in a Post Keynesian micro/macro perspective. It engages in the debate on the effect of price competitive pressures on profit margins. Underlying the ability of firms to transfer the constraint of price pressures to other agents in the economy, and the role of credit discrimination by banks, the paper focuses on the case of a transfer to suppliers and/or subcontractors. We then build a macroeconomic model of a disaggregated economy to show the global consequences of such a mechanism. Simulations suggest that price competition doesn’t lead to a reduction in profit margins but rather to increased wage inequalities. Furthermore, the effect on employment of price pressures is all the more reduced that these price pressures are transferred to other agents.